2021
DOI: 10.3389/fneur.2020.608000
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Antiplatelet Agents for Adult Patients With Ischemic Moyamoya Disease

Abstract: Background: The use of antiplatelet agents in ischemic moyamoya disease (MMD) is controversial. This study aimed to investigate the effectiveness and safety of antiplatelet therapy compared with conservative treatment and surgical revascularization in ischemic MMD patients.Methods: Ischemic MMD patients were retrospectively enrolled from eight clinical sites from January 2013 to December 2018. Follow-up was performed through clinical visits and/or telephone interviews from first discharge to December 2019. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(40 citation statements)
references
References 32 publications
0
32
0
Order By: Relevance
“…23 However, a large-scale study has confirmed the effectiveness of aspirin in preventing further ischemic attacks after adult ischemic MMD. 24 There have also been a few reports testing the outcomes of perioperative aspirin administration. [25][26][27] Rashad et al 26 reported that strict blood pressure control and aspirin administration can reduce the potential risk of surgical complications in combined revascularization for pediatric patients with MMD.…”
Section: Observationsmentioning
confidence: 99%
“…23 However, a large-scale study has confirmed the effectiveness of aspirin in preventing further ischemic attacks after adult ischemic MMD. 24 There have also been a few reports testing the outcomes of perioperative aspirin administration. [25][26][27] Rashad et al 26 reported that strict blood pressure control and aspirin administration can reduce the potential risk of surgical complications in combined revascularization for pediatric patients with MMD.…”
Section: Observationsmentioning
confidence: 99%
“…Surgical intervention was superior as it had the longest interval period between further strokes and it reduced the rate of further cerebral ischemic events (1.9%) compared to the antiplatelet therapy group (5.7%) and the conservative management group (15.1%). [13] A large Korean national retrospective cohort study observed patients with MMD from 2002 to 2016 and it showed strong evidence that the use of antiplatelet therapy decreased mortality by two thirds in those patients compared to non-antiplatelet use. [14] In this case, the radiographic imaging combined with the clinical presentation of the patient supports the diagnosis of Moyamoya disease.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to hemorrhagictype MMD, surgical revascularization is employed to prevent recurrent stroke and improve neurological dysfunctions (10)(11)(12)(13). For ischemic-type MMD, antiplatelet therapy is inferior to surgical revascularization while superior to conservative management for changing the blood supply and preventing future stroke events (37). Revascularization surgery is capable of reducing the recurrence of future stroke for patient with hemorrhagic MMD, but it has not shown an advantage over conservative treatment for patients with ischemic MMD (14,38).…”
Section: Discussionmentioning
confidence: 99%